Lower weight loss expectations and healthier eating attitudes in older overweight and obese women attempting weight loss. Issue 3 (15th April 2015) - Evans, E. H.; Boothroyd, L. G.; Muscariello, E.; Stephan, B. C. M.; Nasti, G.; Colantuoni, A.; Siervo, M.
Abstract : Summary: Weight loss outcomes in overweight and obese individuals may be influenced by individual weight loss expectations (WLEs). Research on these phenomena in older women is lacking. This cross‐sectional study compared groups of younger and older women on their WLEs and related attitudes (body dissatisfaction and disordered eating). Twenty‐six younger (18–38 years) and 33 older (60–78 years) overweight and obese women were recruited from a weight loss clinic, prior to treatment. Disordered eating attitudes and body dissatisfaction were assessed using validated questionnaires and a pictorial figure‐choice scale. Participants reported 10 WLEs categorized according to personal, lifestyle and social factors. Overall, women with a higher body mass index had greater WLEs. Older women reported lower WLEs than younger women (−14.5 kg vs. −22.4 kg) in all categories except past weight. Older women perceived that career success would necessitate the greatest level of weight loss (−18.5 kg), whereas younger women derived their greatest WLEs from mass media (−28.5 kg). Both older and younger groups perceived that their families would be supportive of the smallest amount of weight loss (−8.4 and −17.6 kg, respectively). The groups did not differ on body dissatisfaction, but younger women's disordered eating attitudes were significantly higher ( p < .001). Older overweight and obese women have lower WLEs than younger women but experience similar levels of body dissatisfaction and healthier eating attitudes. The attitudinal constructs underlying these differences may be useful in clinical practice to tailor age‐specific weight loss interventions.